Gender Construction in Manhaj Salaf's Account: A Study of Hadith Content on the Existence of Women in Public Sphere - Mundzir, Muhammad (DINIKA : Academic Journal of Islamic Studies, 2021)
This paper aims to discuss the gender construction of the ‘Manhaj Salaf’ account which regularly posts religious narratives containing hadith. The author specifically tried to read the gender construction of this account through the hadiths about the existence of women. In this case, the author read the contents carefully, then analyzed it with discourse analysis theory and classified it according to the typology of gender discrimination. In addition, the author also look at the implications and effects of the content on the lives of social media users. This study concluded that the Manhaj Salaf account has a bias understanding in narrating the content of hadith, especially about the existence of women. This is proven by its textual and subjective understanding in it. It also raises a negative and positive implications for social media users.